LabTutor - Eaton, John K. (Oxford University Press, 1995)
LabTutor, a combined book and software system, provides an introduction to the principles and practice of laboratory data acquisition, experimental control, and data processing using any hardware/software system. It includes specific instructions and examples on how to use LabVIEW, a graphical programming language from National Instruments used for developing automated instrumentation systems. LabTutor allows new users to make effective use of laboratory computers with as little as ten hours of effort and to become accomplished practitioners with less than forty hours of effort. The printed version offers the convenience and readability of an ordinary book, while the hypertext version includes sound and animation to clarify certain concepts and offers the advantage of rapid searching, making it useful as an online manual. LabTutor can be used as a primary package for a course on laboratory computers, as a supplement in traditional laboratory courses, or as a self-guided tutorial for those learning to use laboratory computers on their own